1971
DOI: 10.1119/1.1986367
|View full text |Cite
|
Sign up to set email alerts
|

Are Colleges Concerned with Intellectual Development?

Abstract: The assumption is often made by college professors that incoming freshman students think logically. Using tests designed by the Swiss psychologist Jean Piaget to evaluate logical thought processes, the authors found that 66 of 131 freshmen exhibited characteristics of the concrete operational thinker, while another 32 did not meet the criteria for formal operations. Professors further compound the problem by failing to recognize the kinds of experiences incoming freshmen students must have to move toward more … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

4
59
3
6

Year Published

1973
1973
2017
2017

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 158 publications
(73 citation statements)
references
References 0 publications
4
59
3
6
Order By: Relevance
“…It may not be that simple. Recent work indicates that many individuals who should chronologically be at Piaget's formal operations level are still at the concrete level (3,4). Many responses of the Low EC group may indicate a concrete operational level of thinking.…”
Section: Methodsmentioning
confidence: 95%
“…It may not be that simple. Recent work indicates that many individuals who should chronologically be at Piaget's formal operations level are still at the concrete level (3,4). Many responses of the Low EC group may indicate a concrete operational level of thinking.…”
Section: Methodsmentioning
confidence: 95%
“…Galileo's further use of the abstraction of an infinitely smooth plane is inconceivable to the 50% of students who are still at Piaget's concrete operational stage. See Renner and Paske Need to Emphasize Epistemology in Teaching and Research 335 (1977), Prigo (1978) and Mckinnon and Renner (1971) Details are shown in Fig. 1 (based on Renner and Paske 1977).…”
Section: Implications For Teachingmentioning
confidence: 98%
“…Linn & Thier (1975) found that fifth graders who were taught using the SCIS materials performed better than those who did not on tasks that required identification and compensation of variables. Several studies noted general gains in reasoning skills and in proportional reasoning for students who experienced instruction using the learning cycle model (McKinnon & Renner, 1971;Renner & Lawson, 1975;Wollman & Lawson, 1978). Finally, a number of studies assessed the development of formal thinking skills among students who experienced either learning cycle or traditional instruction.…”
Section: Developing Scientific Reasoningmentioning
confidence: 99%